Microwave sensors loaded with metamaterial-inspired resonators for dielectric material characterization: A review - Sim, Man Seng; You, Kok Yeow; Dewan, Raimi; Esa, Fahmiruddin; Salim, Mohd Rashidi; Khe, Cheng Seong; Kew, Stephanie Yen Nee; Hamid, Fandi (Elsevier, 2024)
The superior performance of metamaterial-inspired sensors has enabled their application in various material characterization tasks, such as dielectric constant measurement, concentration determination, composition quantification, and impurity or defect detection. This article provides a comprehensive review of recent ad vancements in metamaterial-inspired sensors, with a specific focus on their design aspects. The applications, working principles, and classifications of these sensors are systematically introduced. A novel classification system for metamaterial-based sensors is proposed to categorize them based on their measurement systems, which are planar transmission lines, cavity waveguides, and free-space measurements. Each metamaterial-loaded measurement system is analysed, considering excitation techniques for resonators and the loading configuration of samples under test. Design strategies, including resonator and sensor topology optimization, appropriate material selection, advanced fabrication and data processing techniques, and simplified operations, are reviewed. Lastly, current challenges, encompassing instrumental, sample-related, and application challenges, are addressed. It is envisioned that the design strategies are useful in the development of microwave sensors with enhanced sensitivity, selectivity, accuracy, and robustness.